Distribution of Heritage Association of Harta Pusaka Tinggi And Harta Pusaka Rendah in Padang Pariaman - Elfia, Elfia; Meirison, Meirison; Muhammadi, Qasim (Faculty of Sharia and Law, Universitas Islam Negeri (UIN) Walisongo Semarang, 2020)
This research is motivated by a phenomenon of the distribution of inheritance that occurs in the Nagari Lurah Ampalu community. They hand over inheritance (pusako rendah) at the pusaka tingg